Implementation Of The Employment Guarantee Program In An Effort To Improve The Psychological Well-Being Of Employees Of The South Sidoarjo Pratama Tax Service Office - Rockyanto; Rahayu, Sri; Sundjoto; Fitrianty, Rifda (Neo Journal of economy and social humanities, 2024)
Labor social security is needed by informal sector workers or workers outside the relationship. One of the employment security programs established under the auspices of the DGT is CBB (Perkumpulan Cakti Budddhi Bhakti). This research examines what the implementation of the CBB employment guarantee program in the South Sidoarjo Pratama Tax Service Office looks like, then find out how to improve the psychological well-being of employees of the South Sidoarjo Pratama Tax Service Office, with the implementation of the CBB employment guarantee program and to find out effective strategies in realizing the implementation of the CBB employment guarantee program. This research was conducted on 5 resource persons representing each division in the South Sidoarjo Pratama Tax Service Office. This research uses descriptive qualitative research methods with a case study approach. The data collection method was carried out by interview. The results of the study found that the implementation of the CBB job guarantee program is quite good, but there are still obstacles in the field. One of them is the delivery of knowledge information about the CBB work guarantee program is still very minimal, the implementation of the CBB work guarantee program can improve the psychological well-being of employees of the South Sidoarjo Pratama Tax Service Office, and strategies that can be done to improve the implementation of the CBB work program, one of which is to involve the central party as the authority for this program, in socializing to all DGT employees without exception.